Response Of Growth Of Aren (Arenga pinnata Merr) Growth With Growth Regulatory Substances And Planting Media In The Nursery: Respons Pertumbuhan Bibit Tanaman Aren (Arenga pinnata Merr) Dengan Pemberian Zat Pengatur Tumbuh Dan Media Tanam Di Pembibitan - Yetti Elidar; Purwati (Agrifarm : Jurnal Ilmu Pertanian, 2021)
This study aims to determine the best concentration of ZPT and planting media on the growth of sugar palm plants in nurseries. The research was conducted at Jalan Batu Besaung, Sempaja Utara Village, Samarinda from October 2019 to April 2020. Two-factor factorial experiments were arranged in a completely randomized design with five replications. The first factor was the concentration of ZPT which consisted of four levels, namely, 0 mL L-1 , 1.5 mL L-1 , 3.0 mL L-1 , 4.5 mL L-1 . The second factor consists of four levels of planting media, namely soil (control), soil + husk (2: 1), soil + bokashi (2: 1), soil + husk + bokashi (1: 1: 1). Data were analyzed using variance and continued with the least significant difference test at 5% level. The results showed that the interaction between the concentration of ZPT and planting media (ZxM) was significantly different on the growth of sugar palm in the nursery on the observation variable of the number of leaves aged 120 and 150 DAS. Best interaction is z0m2 at the age of 150 HST. The best concentration of ZPT was at a concentration of 3.0 mL LZPT-1 which showed an increase in sugar palm growth in the observation variables of leaf length, number of leaves, and stem circumference. The best treatment of planting media, namely soil media + husk (2: 1) can increase the growth of sugar palm in the observation variables of midrib length, primary root length, and stem circumference Kata kunci: planting media, sugar palm plants, growth regulators, growt